Body measurement estimations using 3D scanner for individuals with severe motor impairments - Nuzzi, Cristina; Ghidelli, Marco; Luchetti, Alessandro; Zanetti, Matteo; Crenna, Francesco; Lancini, Matteo (2023 IEEE International Symposium on Medical Measurements and Applications (MeMeA), 2023)
In biomechanics, a still unresolved question is how to estimate with enough accuracy the volume and mass of each body segment of a subject. This is important for several applications ranging from the rehabilitation of injured subjects to the study of athletic performances via the analysis of the dynamic inertia of each body segment. However, traditionally this evaluation is done by referring to anthropometric tables or by approximating the volumes using manual measurements. We propose a novel method based on the 3D reconstruction of the subject's body using the commercial low-cost camera Kinect v2. The software developed performs body segment separation in a few minutes leveraging alpha shape approximation of 3D polyhedrons to quickly compute a Montecarlo volume estimation. The procedure was evaluated on a total of 30 healthy subjects and the resulting segments' lengths and masses were compared with the literature.